2023
DOI: 10.1111/fwb.14051
|View full text |Cite
|
Sign up to set email alerts
|

Invaders they are a‐changing: A recent, unexpected surge of invasive loaches in Catalonia

Abstract: † Don't speak too soon, for the wheel's still in spin, and there's no telling who that it's naming (Bob Dylan, The times they are a-changing).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…may jeopardize restoration efforts (Chen, Su, et al, 2020 ; Dorenbosch & Bakker, 2012 ; Gu et al, 2018 ). Recently, the fast recovery of fish biomass and dominance by benthivorous fish in subtropical and tropical lakes have been widely observed (Clavero et al, 2023 ; Roshni et al, 2022 ). Therefore, it is essential to reveal the effects of benthivorous fish disturbance on submerged plants.…”
Section: Introductionmentioning
confidence: 99%
“…may jeopardize restoration efforts (Chen, Su, et al, 2020 ; Dorenbosch & Bakker, 2012 ; Gu et al, 2018 ). Recently, the fast recovery of fish biomass and dominance by benthivorous fish in subtropical and tropical lakes have been widely observed (Clavero et al, 2023 ; Roshni et al, 2022 ). Therefore, it is essential to reveal the effects of benthivorous fish disturbance on submerged plants.…”
Section: Introductionmentioning
confidence: 99%
“…), and catfishes (e.g., I. punctatus and C. gariepinus ) used in aquaculture, because they encompass the most recent and frequent introductions recorded in FishBase. Nonetheless, their ranges may increase globally as global warming facilitates their acclimatization in aquaculture facilities, although any fish species can likewise become established (Clavero et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…During the last period (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013), the analysis of the Fishbase dataset suggested a decrease in the number of introductions. However, considering recent studies highlighting the unexpected surge of certain fish species previously deemed to have low invasion potential (e.g., Clavero et al, 2023), it can be concluded that this finding most probably reflects a recording lag in Fishbase. Fishbase is one of the most comprehensive databases on fish introductions (Casal, 2006;Maldonado et al, 2015;Ruesink, 2005), but it has been shown that new records of alien species need several years to be comprehensively made available (Seebens et al, 2020).…”
Section: F I G U R Ementioning
confidence: 90%
“…Carassius auratus) or as a consequence of the aquarium trade (e.g. Aphanius fasciatus, Poecilia reticulata and Misgurnus bipartitus) (Maceda-Veiga et al 2013;Clavero et al 2023), whereas few of them became naturalised through escapes from fish farm facilities (e.g. Ictalurus punctatus) (Elvira and Almodóvar 2001;Maceda-Veiga et al 2013).…”
Section: Patterns In Aquatic Nis Introductionmentioning
confidence: 99%